Numerical analysis of one-dimensional consolidation of soft clays subjected to cyclic loading and non-Darcian flow - Satwik C.S.; Chakraborty M. (My University, 2025)
This paper aims in understanding the impact of the cyclic load on the one-dimensional consolidation of soft clays subjected to non-Darcian fluid flow. Three different cyclic loadings, namely, trapezoidal, triangular, and haversine, are considered with and without the rest period. The analyses are carried out using the fully implicit scheme of the finite difference method. The hydraulic boundary surfaces are considered either to be pervious or impervious. Unlike for conventional constant loading, negative excess pore water pressure develops during the unloading phase of cyclic load. With the continuation of load application and load removal, the soil reaches a certain equilibrium stage beyond which soil deformation remains confined within a specific elastic range. To verify the impact of flow law on the progress of cyclic-load-induced consolidation, the relevant curves are drawn for a few specific spatial points as well as for the entire layer. The deviation of the curves generated from the Darcian and non-Darcian flow is markedly visible, especially after the attainment of steady-state. The existence of a critical rest period, at which the chosen flow law influences elastic rebound most, is established. © 2022 Elsevier Ltd